Long-term survival after TAVR in patients with low flow-low gradient vs high gradient aortic valve stenosis. (3rd October 2022) - Cardaioli, F; Nai Fovino, L; Rodino', G; Fabris, T; Napodano, M; Massussi, M; Scotti, A; Fraccaro, C; Masiero, G; Lorenzoni, G; Continisio, S; Montonati, C; et al.
Abstract: Introduction: Transcatheter aortic valve replacement (TAVR) has become the treatment of choice in elderly patients affected by severe aortic stenosis (AS). In patients with low-flow low-gradient (LFLG) AS, a clear benefit of TAVR over conservative treatment has been demonstrated. Notwithstanding, patients with classical LFLG (cLFLG) AS have shown worse early post-procedural outcomes compared to those with high-gradient (HG) AS. Purpose: Given the absence of data, we aimed to evaluate long-term survival (up to 10 years) after TAVR in patients with cLFLG and paradoxical LFLG (pLFLG) AS as compared to those with HG-AS. Methods: Consecutive patients undergoing TAVR at our center with a minimum 5-year follow up (i.e. treated between June 2007 and December 2016) were considered for this analysis. According to baseline echocardiography, patients were divided in three groups: 1) HG-AS (MG >40 mmHg); 2) cLFLG-AS (MG <40 mmHg, EF <50%); and 3) pLFLG-AS (MG <40 mmHg, EF >50%). The study endpoint was post-procedural all-cause mortality. To test differences in long-term outcomes among groups, survival curves using the Kaplan Meier estimator were plotted and compared with the log-rank test. To adjust for possible baseline confounders, a propensity score weighted survival analysis was then performed (standard mean deviation <0.1 for all the considered covariates). Results: A total of 574 subjects were included in the analysis (419 [73%] HG-AS; 91 [15%] pLFLG-AS; and 64 [11%] cLFLG-AS). Median survival time was 4.8 years [IQR 2.3–6.2], with a maximum of 12.3 years. Patients with cLFLG-AS presented higher baseline cardiovascular risk compared to those with both HG-AS and pLFLG-AS. At unadjusted survival analysis, patients with cLFLG-AS showed the worst long-term prognosis after TAVR (overall log-rank test p=0.023). However, after propensity weighted adjustment, the long-term survival of patients with cLFLG-AS was similar to those with HG-AS (p=0.77). Patients with pLFLG and HG-AS presented similar survival rate. Unadjusted (Panels A and C) and adjusted (Panels B and D) survival curves are reported in Figure 1. Out of 64 patients with cLFLG-AS, 43 (67%) presented an improvement in LV-EF (>15% from the baseline value) within the first year after TAVR. LV-EF improvement, but not baseline LV-EF, was apparently related to longer post-TAVR survival (Figure 2). Conclusion: In the current study, patients with cLFLG-AS had worse long-term survival after TARV as compared to either HG or pLFLG-AS subjects. This difference was not present after adjusting for possible baseline confounders. Thus, the low-flow state condition per se might have a lower impact on long term prognosis of TAVR patients than previously hypothesized. Post-TAVR LV-EF recovery was common among patients with cLFLG-AS and was associated with improved long-term survival. Funding Acknowledgement: Type of funding sources: None.